Historical center and urban planning in Costa Rica - Chang-Albizurez, Dominique (2020)
This article shows the first results existing of the legal framework for the management of Historical Centers as part of the territory, particularly of the Liberia situation as part of the project “Baseline for the sustainable management of the Historical Center of Liberia City”. The project reviews a brief documentary analysis and a systematic review of the laws, regulations, and case law concerning the historical centers as a heritage property and the territory’s resources from the municipal power perspective of establishing legal instruments for the management of the territory and urban planning. Following the Kelsen pyramid about the hierarchical regulatory system, there were selected executive laws, decrees, and rules, as well as related case law with a heritage property as part of the territory, for the present paper there were no considerations of the international conventions about heritage property since this was addressed comprehensively in other projects. The contribution of this article is to identify the regulatory framework that sustains the municipal regulation as the management tool for heritage conservation of the Historical Center.